2013
DOI: 10.7863/ultra.32.11.2037
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Sonographic Diagnosis of Tonsilloliths

Abstract: Tonsilloliths are calcified concretions that develop in tonsillar crypts. They are usually asymptomatic; however, they may cause problems such as halitosis, dysphagia, a globus sensation, and otalgia. Tonsilloliths may be diagnosed by a simple inspection or palpation of tonsillar crypts, which can be confirmed by panoramic radiography, computed tomography, or magnetic resonance imaging. We report 3 cases of tonsilloliths diagnosed by transoral sonography that was performed easily and comfortably in an office-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…Ultrasonography can also be used for the detection of soft tissue calcifications [18]. In the literature, it was reported that tonsilloliths could be diagnosed by an intraoral transducer [19]. Ultrasonography has some limitations, such as patient discomfort and difficulty of use [19].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography can also be used for the detection of soft tissue calcifications [18]. In the literature, it was reported that tonsilloliths could be diagnosed by an intraoral transducer [19]. Ultrasonography has some limitations, such as patient discomfort and difficulty of use [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the detection of palatine tonsilloliths varies, and the prevalence in CT is 16.0-46.6% and in panoramic radiographs -7.3-13.4% only [7]. Two-dimensional image, superimposition of structures, distortion, and magnification may be diagnostic challenges in interpretation of panoramic radiographs [2,9,13,19]. The detection of TLs in panoramic radiographs might be related to their amount, degree of calcification, or size [4].…”
Section: Discussionmentioning
confidence: 99%
“…They may be asymptomatic or cause dysphagia, globus sensation, halitosis, otalgia, peritonsil-lar abscess, swelling in the tonsillar fossa, glossopharyngeal neuralgia, orofacial pain, upper airway obstruction, and sleep breathing disorders. They may be incidentally found in three-and two-dimensional radiological examinations [1][2][3][4][5][6][7][8][9][10][11][12][13]. TLs appear as small opacities, overlapping the middle portion of mandible ramus, or as multiple poorly defined radio-opacities, which may be oval, round, or irregular in shape, superimposed on the soft tissues' shadows.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several conflicting definitions of tonsilloliths in the literature. Many studies emphasize that tonsilloliths are calcified concretions [1][2][3][4][5][6][7][8]13,19 ; however, calcification is not necessary for a concretion to be considered a tonsillolith. This is evidenced by only 12% of patients with tonsilloliths exhibiting calcification ( Table 3).…”
Section: Tonsillolith Definitionmentioning
confidence: 99%